On-farm study: cytokine profiles and vaginal microbiome of Bos indicus cattle before artificial insemination - Smith, Molly S.; Soffa, Dallas R.; McAnally, Brooke E.; Hickman-Brown, Kyle J.; Stockland, Erin L.; Poole, Rebecca K. (Frontiers in Animal Science, 2024)
Prior studies in beef cattle have shown shifts in the reproductive microbiome prior to artificial insemination (AI), yet few have characterized both the reproductive microbiome and immune responses prior to AI, particularly in purebred Bos indicus. Therefore, the aim of this study was to characterize the circulating cytokines and the vaginal microbiome of Bos indicus females prior to fixed-time artificial insemination (FTAI). Bos indicus females (n = 79) on four separate ranch operations within a 20-mile radius in East Texas were subjected to the 7-day CO-Synch + controlled intervaginal drug-releasing (CIDR) protocol beginning on day (d)-9 with FTAI on d0. Blood samples were collected on d-9 (CIDR IN), d-2 (CIDR OUT), and d0 (AI DAY) for cytokine concentration analyses using the RayBiotech Quantibody Bovine Cytokine Array Q1 kit per the manufacturer's instructions. Sterile vaginal swabs were inserted past the vulva, rotated, and stored at -80°C for microbiome analysis. Bacterial community analyses targeted the V4 hypervariable region of the 16S rRNA gene. Pregnancy status was determined by transrectal ultrasonography with resulting open females (n = 45) and pregnant females (n = 34). Regardless of pregnancy status, the vaginal relative abundance of Firmicutes differed between CIDR IN, CIDR OUT, and AI DAY (63.74% vs. 28.31% vs. 60.86% ± 3.66%, respectively; P < 0.01). Genera with phylum Firmicutes including Ruminococcus, Clostridium, Blautia, Butyrvibrio, and Mogibacterium followed a similar trend (P < 0.05). Butyrvibrio tended to have greater relative abundance in the vaginal samples of Cows than Heifers (4.17% ± 0.75% vs. 3.26% ± 0.77%; P = 0.07). Concentrations of the interferon (IFN)γ (2005.98 ± 471.94 pg/mL vs. 1185.40 ± 482.65 pg/mL; P < 0.01), interleukin (IL)1F5 (153.89 ± 141.07 pg/mL vs. 627.30 ± 149.28 pg/mL; P < 0.01), and interferon gamma-induced protein (IP)10 (9363.26 ± 2929.83 pg/mL vs. 5905.53 ± 2983.60 pg/mL; P = 0.05) were greater in Cows than Heifers. There was a parity-by-status interaction for IP10, with Open Cows having the greatest concentration compared all other groups (P < 0.05). These results indicate differences in circulating cytokines and shifts in the vaginal microbiome for in Bos indicus cattle prior to FTAI.